Regulatory effects of tea polysaccharides on hepatic inflammation, gut microbiota dysbiosis, and serum metabolomic signatures in beef cattle under heat stress - Li, Fan; Xu, Jun; Xie, Min; Fei, Dan; Zhou, Yaomin; Li, Xiong; Guang, Yelan; Gong, Lihui; Hu, Lizhen; Feng, Fan (Frontiers in Physiology, 2024)
Long-term heat stress (HS) severely restricts the growth performance of beef cattle and causes various health problems. The gut microbiota plays a crucial role in HS-associated inflammation and immune stress involving lymphocyte function. This study investigated the effects of dietary tea polysaccharide (TPS), a natural acidic glycoprotein, on HSinduced anorexia, inflammation, and gut microbiota dysbiosis in Simmental beef cattle. The cattle were divided into two groups, receiving either normal chow or normal chow plus TPS (8 g/kg, 0.8%). Hepatic transcriptomics analysis revealed that differentially expressed genes in TPS-fed cattle were primarily enriched in immune processes and lymphocyte activation. TPS administration significantly reduced the expression of the TLR4/NF-κB inflammatory signaling pathway, alleviating HS-induced hepatic inflammation. Gut microbiota analysis revealed that TPS improved intestinal homeostasis in HS-affected cattle by increasing bacterial diversity and increasing the relative abundances of Akkermansia and Alistipes while decreasing the Firmicutes-to-Bacteroidetes ratio and the abundance of Agathobacter. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis indicated that TPS significantly increased the levels of long-chain fatty acids, including stearic acid, linolenic acid, arachidonic acid, and adrenic acid, in the serum of cattle. These findings suggest that long-term consumption of tea polysaccharides can ameliorate heat stress-induced hepatic inflammation and gut microbiota dysbiosis in beef cattle, suggesting a possible liver-gut axis mechanism to mitigate heat stress.